Oxytocin Massage To Reduce Pain Level At Mother’s Post Caesarea Sectio - Kardina Hayati; Lasma Roma Ito Hasian (JURNAL KEBIDANAN KESTRA (JKK), 2022)
Pain is experienced by all post Caesarean mothers which can be reduced by massage techniques. Massage is thought to release the hormone oxytocin which is useful in contracting the uterus. This type of research is a pre-experimental design with one group pre-test and post-test with a significant level of 95% (p ? 0.05). Data analysis uses paired sample t-test. The population came from all post sectio caesarea patients in the inpatient room with a total sample of 14 respondents. The results of this study indicate there is an effect of giving oxytocin massage to the pain value as evidenced by the value of p = 0,000. The results of the mean pain before treatment 5.50 and the mean pain after treatment 2.71. Oxytocin massage can stimulate the hormone oxytocin which can increase milk production, reduce the risk of bleeding, provide comfort and reduce pain. Oxytocin massage can be used as a procedure for maternal care after a caesarean section.